2006
DOI: 10.1185/030079906x112534
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of levalbuterol metered dose inhaler in pediatric patients with asthma: a double-blind, randomized, placebo- and active-controlled trial

Abstract: In this study, levalbuterol administered via MDI significantly improved airway function in comparison with placebo in asthmatic children aged 4-11 years with a safety profile that was similar to placebo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 26 publications
1
10
0
4
Order By: Relevance
“…These factors are not well understood but could relate to solution formulation, emitted MDI dose, particle size, or local absorption and metabolism differences. Consistent with prior reports 8,11,12 for subjects receiving racemic albuterol HFA, the (S)-albuterol plasma concentration reached at least a 4-fold higher level than the (R)-albuterol plasma concentration. These high levels of (S)-albuterol in the subjects administered racemic albuterol were not associated with impaired bronchodilatory response in this study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These factors are not well understood but could relate to solution formulation, emitted MDI dose, particle size, or local absorption and metabolism differences. Consistent with prior reports 8,11,12 for subjects receiving racemic albuterol HFA, the (S)-albuterol plasma concentration reached at least a 4-fold higher level than the (R)-albuterol plasma concentration. These high levels of (S)-albuterol in the subjects administered racemic albuterol were not associated with impaired bronchodilatory response in this study.…”
Section: Discussionsupporting
confidence: 91%
“…4 FEV 1 values improved similarly for subjects administered levalbuterol HFA MDI and racemic albuterol HFA MDI over the cumulative dosing regimen, which is consistent with a report that evaluated the efficacy of these 2 therapies in asthmatic children aged 4 to 11 years. 8 A prior cumulative dose study comparing levalbuterol and racemic albuterol delivered by means of nebulization reported similar improvements in FEV 1 , changes in heart rate, and serum potassium concentration for the 2 treatments. 4 This previous study also reported a similar therapeutic ratio for the 2 treatments.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…There have been rare reports concerning the use or abuse of levalbuterol (2). Two reports note that QT prolongation and hypokalemic effects of levalbuterol are similar to racemic albuterol (3,4).…”
mentioning
confidence: 97%
“…For asthma and chronic bronchitis, proper use of inhaled bronchodilators can relieve shortness of breath and wheeze. They have been shown to be effective, (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) with a low incidence of adverse events. (10,(15)(16)(17) Therefore, fi rst aid providers should be familiar with the available inhaled bronchodilator and assist when a casualty with asthma or chronic bronchitis is experiencing an acute exacerbation of the condition.…”
Section: Medicalmentioning
confidence: 99%